Recursos tecnológicos y su influencia en el aprendizaje de estudios sociales en estudiantes de la UE Adolfo Maria Astudillo, Babahoyo - Sarango Ramos, Byron Leonardo (2022)
Technological resources, worldwide, are tools of important value, especially for students, since they allow the development of academic activities, which facilitates teaching-learning processes and the connection between teacher-student. The management of digital tools to implement the new teaching methodology for students and teachers to be able to provide such knowledge, in some cases it is positive, but it should be noted that not all students have the resources to enter this type of methodology, and areas of learning in which the student must have a diversified education is almost nil. The use of technological tools to continue with the teaching-learning process, it was evidenced that, in academic performance and acquisition of competence. The purpose of this project is to improve the academic performance in the subjects of the students "UNIDAD EDUCATIVA ADOLFO MARIA ASTUDILLO BABAHOYO" where teachers must use their best effort in order to achieve adequate teaching so that students have a performance of high quality, taking as a sample the area of Social Studies. Keywords: Technological Resources, Academic Performance, Teaching.